Pengaruh Minat Baca Terhadap Prestasi Belajar Bahasa Indonesia Siswa Kelas V SD Negeri 0304 Siundol - Karmila Lahagu; Nurhayati Siregar; Nurhalimah Harahap (CV. Alim's Publishing, 2023)
This research aims to determine the influence of interest in reading on the Indonesian language learning achievement of class V students at SD Negeri 0304 Siundol, Sosopan sub-district, Padang Lawas district. This type of research is quantitative research with experimental methods. The population in this study were all fifth grade students at SD Negeri 0304 Siundol, sampling was taken using total sampling. The research instruments were the distribution of questionnaires and tests. Based on the calculations carried out, it shows that the average reading interest is 50.13, the maximum value is 90, the minimum value is 60. The post test average > pre test average (78.59 > 44.68). The results of the pre-test normality test Lcount < Ltabel (0.1309 < 0.1888) were normally distributed, and the post-test normality test Lcount < Ltabel (0.1570 < 0.1888) were normally distributed. homogeneity test results Fcount < Ftable (1.33 < 2.12) are homogeneous in distribution. The results of hypothesis testing with a level of α = 0.05, that the value of tcount > ttable (5.19 > 1.73) is in accordance with the basic provisions for decision making that Ha is accepted, meaning that there is a significant influence of interest in reading on the learning achievement of fifth grade students at State Elementary Schools. 0304 Siundol.